Gender Differences in Motivations for Identity Reconstruction on Social Network Sites - Huang, Jiao; Kumar, Sameer; Hu, Chuan (Taylor & Francis, 2018)
Social network sites provide people a unique opportunity for self-presentation. Due to various reasons, people may build an online identity that is partly or even completely different from their identity in the real world. Adopting social role theory as the theoretical foundation, the current study investigated gender differences in the motivations for virtual identity reconstruction on QQ, a social network site based in China. A total of 418 respondents participated in the study. As hypothesized, the results showed that men and women are motivated differently when reconstructing their identity–while women focus more on physical vanity, men emphasize achievement vanity. The authors also identified gender differences in other motivations for online identity reconstruction: bridging social capital, disinhibition, and privacy concerns. The results, which suggest that men and women behave in gender-specific ways, are in line with the propositions made in social role theory.